Room or relegation? : a critical analysis of section 77(2)(a) of the Companies Act, 2008, in light of the common law remedy of disgorgement - Stevens, Angela Gail (Department of Commercial Law, 2016)
Corporate heresy 1 or legislative oversight: is there room for the common law remedy of disgorgement under section 77 (2)(a) of the Companies Act2 or has the remedy been relegated to the past? This controversial enquiry frames the groundwork for discussion upon which this dissertation is based. Section 77(2)(a) reads as follows: "(2) A director of a company may be held liable - (a) in accordance with the principles of the common law relating to breach of a fiduciary duty, for any loss, damages or costs sustained by the company as a consequence of any breach by the director of a duty contemplated in section 75, 76 (2) or 76 (3)(a) or (b). ,o This dissertation seeks to shed light on the apparent legislative omission of the common law remedy of disgorgement from the ambit of section 77(2)(a). The effects and consequences of such a significant omission has come under the microscope given South Africa's recently reformed corporate law jurisprudence. The impact of such an omission on the interpretation and application of directors' duties and liabilities will be specifically examined and analysed. The topic of this dissertation remains especially relevant to any discussion involving directors' duties and liabilities in the context of the new Companies Act ("the Act"). The Act has drastically reshaped the South African corporate law landscape and as such, each provision of the Act requires careful consideration in its interpretation and application. Implementation of the Act, in 2011, brought about partial codification of directors' duties and liabilities. Partial codification has resulted in mandatory, unalterable and prescriptive provisions relating to directors' duties and liabilities which are applicable to all companies registered in the Republic.• Since its inception, critics have intimated that certain provisions of the Act hinder, as opposed to facilitate, the objective of clarifying directors' duties and liabilities.5 Fear of statutory liability gives further credence to the importance of clear, concise and uniform interpretation and application of the statutory duties. The statutory duties and liabilities do not replace their common law equivalents. Interpretation, application and development of the statutory duties and liabilities must align with those embedded in the common law.6 Alignment becomes increasingly difficult, however, when inconsistencies and contradictions between these two primary sources of law run rampant. The provisions of section 77(2)(a), conceivably, showcase such a misalignment between the common law and the Act.